Complete mitochondrial genome of Microphysogobio alticorpus (Cypriniformes, Cyprinidae). (June 2014) - Lin, Der-Yuh; Lin, Hung-du; Tzeng, Shwu-Jen; Chiang, Tzen-Yuh
Abstract In this study, we determined the complete mitochondrial (mt) genome of Microphysogobio alticorpus (Cypriniformes, Cyprinidae). This mt genome, consisting of 16, 568 base pairs (bp), encoded genes for 13 protein-coding genes, 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and a noncoding control region (CR) as those found in other vertebrates, with the gene order identical to that of typical vertebrates. The overall base composition of the heavy strand shows T: 26.03%, C: 26.73%, A: 30.20% and G: 17.04%, apparently with a slight AT bias. The two rRNA genes of 12S rRNA (958 bp) and 16S rRNA (1693 bp) are located between tRNAPhe and tRNALeu(UUR) and separated by the tRNAVal gene. CR, of 890 bp in length, is located between tRNAPro and tRNAPhe.